The critical size of hydrogen-bonded alcohol clusters as effective Brønsted bases in solutions. Issue 36 (24th June 2016) - Park, Sun-Young; Kim, Taeg Gyum; Ajitha, Manjaly J.; Kwac, Kijeong; Lee, Young Min; Kim, Heesu; Jung, Yousung; Kwon, Oh-Hoon
Abstract : Hydrogen-bonded clustering of alcohol molecules increases their basicity (proton affinity) significantly, so that alcohol dimers can accept a proton which otherwise is impossible due to insufficient basicity as a monomer. Abstract : The alkyl oxonium ion, which is a protonated alcohol, has long been proposed as a key reaction intermediate in alcohol dehydration. Nonetheless, the dynamics and structure of this simple but important intermediate species have not been adequately examined due to the transient nature of the oxonium ion. Here, we devised a model system for the key step in the alcohol dehydration reaction, in which a photoacid transfers a proton to alcohols of different basicity in the acetonitrile solvent. Using time-resolved spectroscopy and computation, we have found that the linkage of at least two alcohol molecules via hydrogen bonding is critical for their enhanced reactivity and extraction of the proton from the acid. This finding addresses the cooperative role of the simplest organic protic compounds, namely alcohols, in nonaqueous acid–base reactions.